(untitled) (Latakia University Journal -Biological Sciences Series, 2024)
To compare the effectiveness of the compound Chitosan with some fungicides to control strawberry powdery mildew disease caused by the fungus Podosphaera aphanis, The effectiveness of the compound Chitosan was tested in comparison with three fungicides belonging to different chemical groups, The results showed good and similar effectiveness of the compound Chitosan with the tested fungicides to control the disease. Its effectiveness, based on the percentage of fruit infection 21 days after spraying, reached 73.5%, While the effectiveness of the fungicide Pancho reached 79.7%. While the fungicides chlorothalonil and hexaconazole had (75.1 and 70.5%), respectively. As for the effectiveness results, based on the severity of leaf injury 21 days after spraying, The effectiveness of the compound Chitosan was close to the effectiveness of the chlorothalonil, reaching (75.2 and 75.7%) respectively. The effectiveness of the Pancho reached 81.0%, while it was 73.8% for the hexaconazole.